Analysis Work Discipline on Employee Performance - Yosminaldi Yosminaldi; Fauzobihi Fauzobihi; Ade Irawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The disciplin and employee performance are a unit in the family of human resources science study, work discipline plays an important role in determining the level of performance. The performance of the employee in question can be seen from the work results achieved by employees in terms of quality and quantity in accordance with the employee's duties and responsibilities. Performance is something that can affect the achievement of the company's goals and progress in increasingly fierce competition. In this research, employee work disciplie suggests that performance is one of the elements used in employee assessment which includes discipline to their work, position and organization. This discipline is reflected by the employee's willingness to protect and defend the organization inside and outside of work from being undermined by irresponsible people